An Investigation of Selection Criteria for Admission to an Ontario University - Pollock, Gordon; Bowman, Richard J.; Gendreau, Paul; Gendreau, Lorna (Canadian Journal of Higher Education, 1975)
The study investigated the effectiveness of five methods of university admission criteria in relation to academic results achieved after one year of university study. The admission criteria used were open admission, interview, teacher recommendations, Grade 13 academic achievement and SACU test scores. In addition these procedures were compared with a traditional method of admission at the university where the study was carried out. The characteristics of the admission groups were not significantly related to geographical distribution, sex distribution, government financial assistance, and attitude and personality questionnaire data. These characteristics were no different for these groups than the traditional method of selection and there was no significant difference between groups as to final first year grade point average or academic penalty i.e., probations and rustications. The open admissions group compared favourably on these latter variables with other admissions groups and particularly with the university's traditional method of admission.